Conversion of esters to thioesters under mild conditions. Issue 13 (18th March 2021) - Shi, Yijun; Liu, Xuejing; Cao, Han; Bie, Fusheng; Han, Ying; Yan, Peng; Szostak, Roman; Szostak, Michal; Liu, Chengwei
Abstract : We report conversion of esters to thioesters via selective C–O bond cleavage/weak C–S bond formation under transition-metal-free conditions. Abstract : We report conversion of esters to thioesters via selective C–O bond cleavage/weak C–S bond formation under transition-metal-free conditions. The method is notable for a general and practical transition-metal-free system, broad substrate scope and excellent functional group tolerance. The strategy was successfully deployed in late-stage thioesterification, site-selective cross-coupling/thioesterification/decarbonylation and easy-to-handle gram scale thioesterification. Selectivity and computational studies were performed to gain insight into the formation of weak C–S bonds by C–O bond cleavage, which contrasts with the traditional trend of nucleophilic additions to carboxylic acid derivatives.